The Effect of Cognitive Behavioral Therapy-Based Psychoeducation on Irrational Beliefs, Expressing Emotions, and Mental Well-Being - Elif Gök; Mustafa Uslu (Journal of Research in Social Sciences and Language)
The study aimed to measure how irrational beliefs, emotional expression, and mental well-being levels of high school student participants changed following the psychoeducation intervention. A pre-test–post-test control group experimental design without pairing was used as the research model. Data was collected from twenty high school students, ten in the control group and ten in the experimental group. The Personal Information Form, the Irrational Beliefs Test (IBT), the Emotional Expression Scale (EES), and the Warwick-Edinburgh Mental Well-Being Short Form (WEMWBS) were used in the study. The psychoeducation consisted of eight semi-structured sessions, each lasting 90 minutes. The dataset was analyzed using repeated measures ANOVA with a mixed design. The findings indicate that the level of irrational beliefs in the experimental group decreased significantly more than in the control group. Significant differentiation was observed in the sub-dimensions of approval-seeking and emotional irresponsibility. However, no statistically significant difference was found for the other two variables. The findings of the study were discussed in relation to the relevant literature, and recommendations were provided for researchers and practitioners.